Kalteng Expo 2023: Strategi DISDAGPERIN Prov. Kalteng dalam Mendorong Daya Saing Produk Unggulan Daerah Pasca Pandemi - Putika Saridewi; Safira Rizki Nurfebrina; Ayu Nabila; Sutri Trisna Dahlia; Peridawaty Peridawaty (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
To support economic recovery and increase the competitiveness of superior regional products following the COVID-19 pandemic, the Kalteng Expo 2023 is a regional exhibition. This study aims to determine the Central Kalimantan Provincial Trade and Industry Office's plans to hold the Kalteng Expo 2023 and how it will impact MSMEs and Small and Medium Enterprises (SMEs). Qualitative descriptive research was conducted through observation, interviews, and documentation. The results indicate that the Disdagperin strategy was implemented through booths, collaboration with various parties, and promotion of superior regional products. With a total turnover of approximately IDR 7 billion and approximately 9,000 visitors per day, the expo increased sales and enhanced business networks.